The Research Process - Oleen, Jenny; Marrall, Rebecca (Western Washington University, 2016)
The Research Process: Strategies for Undergraduate Students is an open access textbook written by library, archives, and Learning Commons professionals at Western Libraries, and is intended for undergraduate students. In Getting Started, you will discover the stages inherent in the research process, and be introduced to the available resources at Western Libraries. In Explore, you will explore different information sources, and will learn how to develop robust search strategies for each information source. In Focus & Finalize, you will learn about copyright practices and Fair Use, and how to synthesize your research materials.
Strategies for Undergraduate Students